Elastomer and wearable device therewith
Patent Information
- Application Number
- JP2023067064
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-04-17
- Publication Date
- 2025-03-18
AI Technical Summary
Elastomers used in wearable devices, such as those described in Patent Document 1, exhibit inadequate conformability to irregular surfaces, necessitating an improvement in their ability to follow uneven surfaces.
The elastomer's conformability to irregularities is enhanced by controlling its hardness during elongation, setting the durometer hardness at 50% elongation to be between 20 and 80, measured using JIS K6253, and optimizing the composition and crosslink density through the use of specific silicone rubber components and fillers.
The elastomer achieves improved conformability to irregular surfaces, maintaining mechanical strength and durability while enhancing stretchability and durability, making it suitable for wearable devices that require flexibility and adherence to body contours.
Smart Images

Figure 00000027_0000 
Figure 00000027_0001 
Figure 00000027_0002
Abstract
Description
[Technical Field]
[0001] The present invention relates to an elastomer and a wearable device using the same. [Background technology]
[0002] Various studies have been conducted on elastomers for wearable devices. One known example of this type of technology is the technology described in Patent Document 1. Patent Document 1 describes the use of polyurethane in the stretchable substrate of a wearable device (see paragraph 0031, Figure 2, etc. of Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2018-104869 Summary of the Invention [Problem to be solved by the invention]
[0004] However, the inventors of the present invention have conducted research and found that the elastomer described in Patent Document 1 has room for improvement in terms of its ability to conform to irregularities. [Means for solving the problem]
[0005] The present inventors have found that the ability of an elastomer to conform to an uneven surface can be controlled by using the physical properties in a direction perpendicular to the direction of elongation when the elastomer is stretched as a guideline. As a result of intensive research based on this knowledge, the inventors have found that the elastomer's ability to conform to uneven surfaces can be improved by using the elongated hardness of the elastomer as an indicator and setting the elongated hardness, which serves as an indicator, to a predetermined value or less, and have thus completed the present invention.
[0006] According to the present invention, An elastomer for a wearable device, comprising: The durometer hardness A of the elastomer at 50% elongation when measured using a hardness tester at 25°C in accordance with JIS K6253 (1997) in accordance with the following elongation procedure: 50 is 20 or more and 80 or less. (Decompression operation) (1) A strip test piece of a specified thickness is prepared from the elastomer. (2) Both ends of the strip test piece are placed between the chucks of the stretching machine. (3) The distance between the chucks when the strip test piece changes from a loose state to a taut state is defined as the initial value D0. (4) The distance between the chucks is increased by a predetermined percentage from the initial value D0, and the strip test piece is held in the elongated state by the predetermined percentage for one minute.
[0007] The present invention also provides a wearable device comprising the above-described elastomer. [Effects of the Invention]
[0008] According to the present invention, an elastomer having excellent conformability to uneven surfaces and a wearable device using the same are provided. [Brief explanation of the drawings]
[0009] [Figure 1] FIG. 2 is a diagram illustrating a method for measuring the elongated hardness of an elastomer. [Figure 2] FIG. 2 is a top view schematically illustrating an outline of a stretching machine. [Figure 3] FIG. 1 is a diagram illustrating a method for evaluating the conformability of an elastomer. DETAILED DESCRIPTION OF THE INVENTION
[0010] The elastomer of this embodiment will be outlined below.
[0011] The elastomer of this embodiment has a durometer hardness A of the elastomer at 50% elongation when measured using a hardness tester at 25°C in accordance with JIS K6253 (1997) in a state where the elastomer is elongated by 50% according to the following elongation procedure: 50 It is an elastomer for wearable devices that can have a characteristic of 20 or more and 80 or less.
[0012] (Decompression operation) (1) A strip test piece of a specified thickness is prepared from the elastomer. (2) Both ends of the strip test piece are placed between the chucks of the stretching machine. (3) The distance between the chucks when the strip test piece changes from a loose state to a taut state is defined as the initial value D0. (4) The distance between the chucks is increased by a predetermined percentage from the initial value D0, and the strip test piece is held in the elongated state by the predetermined percentage for one minute.
[0013] In recent years, the demands for wearable devices (wearable equipment) have become even higher in terms of wearability, such as stability and comfort. Focusing on this type of wearability, the inventors thought that such wearability could be improved by improving the ability to conform to unevenness and steps on the surface of the body or the surface of clothing worn on the body. Therefore, the present inventors conducted research and found that the ability of an elastomer to conform to an uneven surface can be controlled by using the physical properties in a direction perpendicular to the elongation direction when the elastomer is stretched as a guideline. Based on this knowledge, the inventors conducted extensive research and found that the ability of an elastomer to conform to an uneven surface can be improved by using the elastomer's hardness at elongation as an indicator and setting the hardness at elongation as an indicator to a predetermined value or less, thereby making it possible to stably evaluate the ability to conform to an uneven surface. Furthermore, the present inventors' research also led to the discovery of a method for measuring hardness at elongation.
[0014] According to the elastomer of this embodiment, the durometer hardness A of the elastomer at 50% elongation 50By making the value of the upper limit or less, it is possible to realize an elastomer having excellent conformability to unevenness.
[0015] A molded article including the elastomer of this embodiment can be applied to, for example, a wearable device that can be attached to the body or clothing. Examples of wearable devices include medical sensors that detect biological phenomena such as heart rate, electrocardiogram, blood pressure, and body temperature, healthcare devices, bendable displays, stretchable LED arrays, stretchable solar cells, stretchable antennas, stretchable batteries, actuators, and wearable computers. The wearable devices can be used as components for constructing movable members (stretchable members) that stretch or bend, such as stretchable electrodes, stretchable wiring, and stretchable substrates, and exterior members. Among these, the elastomer is preferably used in wearable devices that are wrapped around the body or clothing. The elastomer can be processed and molded into various shapes such as a sheet, a tube, or a bag.
[0016] Next, the characteristics of the elastomer of this embodiment will be described.
[0017] The elongated durometer hardness A of an elastomer (hereinafter sometimes simply referred to as "hardness") is measured in a state where the elastomer is elongated by 50% according to the elongation procedures shown in (1) to (4) above. The size of the strip test piece (1) is, for example, width: 5 mm × length: 100 mm, and thickness: 2 mm. The thickness may be 2 mm, or may be between 6 mm and 10 mm. The stretching machine (2) can be a uniaxial stretching machine for film, or it can be a manual stretching machine. (3) A loose specimen strip means that there is almost no stress on either end of the chuck, and a tight specimen strip means that there is only a slight stress on either end of the chuck. The predetermined percentage in (4) above is 50%, 100%, or 200%. The hardness at elongation from 50% to 200% may be measured consecutively. The measurement location for the durometer hardness A of the strip test piece (4) above is, for example, the center of the strip test piece or its vicinity. Measurements may be made using one strip test piece with n=5, and the average value of the measurements may be used as the measured value.
[0018] In the elastomer of this embodiment, the durometer hardness A of the elastomer at 50% elongation at 25°C measured in accordance with JIS K6253 (1997) 50 The lower limit of A may be, for example, 20 or more, preferably 25 or more, and more preferably 30 or more. This can improve the restorability during repeated use. 50 The upper limit is not more than 80, preferably not more than 70, and more preferably not more than 65. This makes it possible to realize an elastomer that is excellent in conformability to irregularities.
[0019] In the elastomer of this embodiment, the durometer hardness A of the elastomer at 100% elongation at 25°C measured in accordance with JIS K6253 (1997) 100 The lower limit of A may be, for example, 25 or more, preferably 30 or more, and more preferably 35 or more. This can improve the mechanical strength. 100 The upper limit of the tensile strength is 85 or less, preferably 80 or less, and more preferably 75 or less. This makes it possible to realize an elastomer with excellent conformability to uneven surfaces. In addition, stretchability and durability when stretched can be improved.
[0020] In the elastomer of this embodiment, the durometer hardness A of the elastomer at 200% elongation at 25°C measured in accordance with JIS K6253 (1997) 200 The lower limit of A may be, for example, 30 or more, preferably 40 or more, and more preferably 50 or more. This can improve the mechanical strength. 200 The upper limit of the value is 90 or less, preferably 85 or less, and more preferably 80 or less. This makes it possible to realize an elastomer with excellent conformability to uneven surfaces. In addition, stretchability and durability when stretched can be improved.
[0021] In the elastomer of this embodiment, the tensile stress M 100 The upper limit of the tensile stress M may be, for example, 7.0 MPa or less, preferably 6.0 MPa or less, and more preferably 5.0 MPa or less. This can improve the ease of deformation of the elastomer. 100 The lower limit of the modulus of elasticity may be 0.1 MPa or more, preferably 0.5 MPa or more, and more preferably 0.8 MPa or more, which can improve the mechanical strength of the elastomer.
[0022] In the elastomer of this embodiment, the tensile stress M 200 The upper limit of the tensile stress M may be, for example, 9.0 MPa or less, preferably 8.0 MPa or less, and more preferably 7.5 MPa or less. This can improve the ease of deformation of the elastomer. 200 The lower limit of the modulus of elasticity may be 0.5 MPa or more, preferably 1.0 MPa or more, and more preferably 1.5 MPa or more, which can improve the mechanical strength of the elastomer.
[0023] In the elastomer of this embodiment, the tensile stress M 200 - tensile stress M 100 ) / tensile stress M 100 ) × 100 is, for example, 110% or less, preferably 100% or less, and more preferably 90% or less. This allows the properties to be balanced. On the other hand, 200 - tensile stress M 100 ) / tensile stress M 100 The lower limit of the ratio (%) × 100 is 10% or more, preferably 15% or more, and more preferably 20% or more, which can increase the ease of deformation of the elastomer.
[0024] (Tensile stress measurement conditions) Tensile stress M 100 : The tensile stress of the elastomer at 100% elongation measured in accordance with JIS K6251 (2004) at 25°C. Tensile stress M200 : The tensile stress of the elastomer at 200% elongation measured in accordance with JIS K6251 (2004) at 25°C.
[0025] In the elastomer of this embodiment, the upper limit of the tear strength TS0 may be, for example, 70 N / mm or less, preferably 68 N / mm or less, more preferably 65 N / mm or less, and even more preferably 60 N / mm or less. This allows the various properties of the elastomer to be balanced. On the other hand, the lower limit of the tear strength TS0 is 25 N / mm or more, preferably 30 N / mm or more, more preferably 35 N / mm or more, and even more preferably 38 N / mm or more. This allows the scratch resistance and mechanical strength of the elastomer to be improved.
[0026] (Tear strength measurement conditions) Tear strength TS0: The tear strength of the elastomer at 25°C measured in accordance with JIS K6252 (2001) of the elastomer.
[0027] In the elastomer of this embodiment, the upper limit of the breaking elongation BE0 may be, for example, 1500% or less, preferably 1200% or less, more preferably 1000% or less, and even more preferably 900% or less. This allows for a balanced set of properties for the elastomer. Meanwhile, the lower limit of the breaking elongation BE0 is 250% or more, preferably 300% or more, and more preferably 350% or more. This allows for improved stretchability and durability of the elastomer.
[0028] (Measurement conditions for breaking elongation) Breaking elongation BE0: The breaking elongation of the elastomer measured at 25°C (room temperature) in accordance with JIS K6251 (2004).
[0029] In this embodiment, the hardness, tensile stress, elongation at break, and tear strength can be controlled by appropriately selecting, for example, the type and blending amount of each component contained in the elastomer, the method for preparing the composition for forming the elastomer, etc. Among these, factors for setting the hardness, tensile stress, elongation at break, and tear strength within the desired numerical ranges include, for example, appropriately controlling the type and blending ratio of the resins constituting the elastomer, the crosslinking density and crosslinking structure of the resin, and improving the blending ratio of the inorganic filler and the dispersibility of the inorganic filler.
[0030] The composition of the elastomer of this embodiment will be described below.
[0031] The elastomer may contain silicone rubber, which is chemically stable and has excellent thermal stability.
[0032] The thermosetting elastomer may be a cured product of a curable elastomer composition, and the silicone rubber may be a cured product of a silicone rubber-based curable composition.
[0033] The molded article of the present embodiment may contain any component capable of exhibiting various functions. For example, the elastomer may contain an inorganic filler to enhance mechanical strength. Known inorganic fillers may be used, such as silica particles.
[0034] Hereinafter, a case where a silicone rubber-based curable composition is used as the silicone rubber, which is an example of the elastomer of this embodiment, will be described.
[0035] The silicone rubber-based curable composition of this embodiment may contain a vinyl group-containing organopolysiloxane (A). The vinyl group-containing organopolysiloxane (A) is a polymer that serves as the main component of the silicone rubber-based curable composition of this embodiment.
[0036] The vinyl group-containing organopolysiloxane (A) can contain a vinyl group-containing linear organopolysiloxane (A1) having a linear structure.
[0037] The vinyl group-containing linear organopolysiloxane (A1) has a linear structure and contains vinyl groups, which become crosslinking points during curing.
[0038] The vinyl group content of the vinyl group-containing linear organopolysiloxane (A1) is not particularly limited, but preferably has two or more vinyl groups in the molecule and is 15 mol% or less, more preferably 0.01 to 12 mol%. This optimizes the amount of vinyl groups in the vinyl group-containing linear organopolysiloxane (A1), ensuring the formation of a network with each of the components described below. In this embodiment, the symbol "to" means that both ends of the symbol are included.
[0039] In this specification, the vinyl group content refers to the mole percent of vinyl group-containing siloxane units when all units constituting the vinyl group-containing linear organopolysiloxane (A1) are taken as 100 mole percent, where it is considered that there is one vinyl group per vinyl group-containing siloxane unit.
[0040] The degree of polymerization of the vinyl group-containing linear organopolysiloxane (A1) is not particularly limited, but is preferably within a range of, for example, about 1,000 to 10,000, and more preferably about 2,000 to 5,000. The degree of polymerization can be determined, for example, as the polystyrene-equivalent number-average degree of polymerization (or number-average molecular weight) measured by GPC (gel permeation chromatography) using chloroform as a developing solvent.
[0041] Furthermore, the specific gravity of the vinyl group-containing linear organopolysiloxane (A1) is not particularly limited, but is preferably in the range of about 0.9 to 1.1.
[0042] By using a vinyl group-containing linear organopolysiloxane (A1) having a degree of polymerization and specific gravity within the above ranges, it is possible to improve the heat resistance, flame retardancy, chemical stability, etc. of the resulting silicone rubber.
[0043] As the vinyl group-containing linear organopolysiloxane (A1), it is particularly preferable that it has a structure represented by the following formula (1).
[0044] [ka]
[0045] In formula (1), R 1 is a hydrocarbon group selected from substituted or unsubstituted alkyl groups, alkenyl groups, aryl groups, or combinations thereof having 1 to 10 carbon atoms. Examples of alkyl groups having 1 to 10 carbon atoms include methyl groups, ethyl groups, and propyl groups, with methyl groups being preferred. Examples of alkenyl groups having 1 to 10 carbon atoms include vinyl groups, allyl groups, and butenyl groups, with vinyl groups being preferred. Examples of aryl groups having 1 to 10 carbon atoms include phenyl groups.
[0046] Also, R 2 is a substituted or unsubstituted alkyl group, alkenyl group, aryl group, or a hydrocarbon group combining these groups, each having 1 to 10 carbon atoms. Examples of alkyl groups having 1 to 10 carbon atoms include methyl, ethyl, and propyl groups, with methyl being preferred. Examples of alkenyl groups having 1 to 10 carbon atoms include vinyl, allyl, and butenyl groups. Examples of aryl groups having 1 to 10 carbon atoms include phenyl groups.
[0047] Also, R 3is a substituted or unsubstituted alkyl group or aryl group having 1 to 8 carbon atoms, or a hydrocarbon group consisting of a combination thereof. Examples of alkyl groups having 1 to 8 carbon atoms include methyl, ethyl, and propyl groups, with methyl being preferred. Examples of aryl groups having 1 to 8 carbon atoms include phenyl groups.
[0048] Furthermore, R in formula (1) 1 and R 2 Examples of the substituent of R include a methyl group and a vinyl group. 3 Examples of the substituent include a methyl group.
[0049] In addition, in formula (1), multiple R 1 are independent of each other and may be different or the same. 2 , and R 3 The same is true for .
[0050] Furthermore, m and n are the numbers of repeating units constituting the vinyl group-containing linear organopolysiloxane (A1) represented by formula (1), where m is an integer of 0 to 2000 and n is an integer of 1000 to 10000. m is preferably 0 to 1000, and n is preferably 2000 to 5000.
[0051] Specific examples of the vinyl group-containing linear organopolysiloxane (A1) represented by formula (1) include those represented by the following formula (1-1).
[0052] [ka]
[0053] In formula (1-1), R 1 and R 2 are each independently a methyl group or a vinyl group, and at least one of them is a vinyl group.
[0054] Furthermore, the vinyl group-containing linear organopolysiloxane (A1) preferably contains a first vinyl group-containing linear organopolysiloxane (A1-1) having two or more vinyl groups in the molecule and a vinyl group content of 0.4 mol% or less, and a second vinyl group-containing linear organopolysiloxane (A1-2) having a vinyl group content of 0.5 to 15 mol%. Combining a first vinyl group-containing linear organopolysiloxane (A1-1) with a typical vinyl group content for raw rubber, the raw material for silicone rubber, with a second vinyl group-containing linear organopolysiloxane (A1-2) with a high vinyl group content allows for uneven distribution of vinyl groups, more effectively creating a crosslink density distribution within the crosslinked network of the silicone rubber. As a result, the tear strength of the silicone rubber can be more effectively increased.
[0055] Specifically, the vinyl group-containing linear organopolysiloxane (A1) may be, for example, a vinyl group-containing linear organopolysiloxane represented by the above formula (1-1), 1 is a vinyl group and / or R 2 a first vinyl group-containing linear organopolysiloxane (A1-1) having two or more units in the molecule in which R is a vinyl group and containing 0.4 mol % or less of the unit; 1 is a vinyl group and / or R 2 It is preferable to use a second vinyl group-containing linear organopolysiloxane (A1-2) containing 0.5 to 15 mol % of units in which each of the units is a vinyl group.
[0056] The first vinyl group-containing linear organopolysiloxane (A1-1) preferably has a vinyl group content of 0.01 to 0.2 mol %, and the second vinyl group-containing linear organopolysiloxane (A1-2) preferably has a vinyl group content of 0.8 to 12 mol %.
[0057] Furthermore, when the first vinyl group-containing linear organopolysiloxane (A1-1) and the second vinyl group-containing linear organopolysiloxane (A1-2) are combined and blended, the ratio of (A1-1) to (A1-2) is not particularly limited, but for example, the weight ratio of (A1-1):(A1-2) is preferably 50:50 to 95:5, and more preferably 80:20 to 90:10.
[0058] The first and second vinyl group-containing linear organopolysiloxanes (A1-1) and (A1-2) may each be used alone or in combination of two or more.
[0059] The vinyl group-containing organopolysiloxane (A) may also contain a vinyl group-containing branched organopolysiloxane (A2) having a branched structure.
[0060] <<Organohydrogenpolysiloxane (B)>> The silicone rubber-based curable composition of this embodiment can contain an organohydrogenpolysiloxane (B). The organohydrogenpolysiloxane (B) is classified into a linear organohydrogenpolysiloxane (B1) having a linear structure and a branched organohydrogenpolysiloxane (B2) having a branched structure, and may contain either one or both of these.
[0061] The linear organohydrogenpolysiloxane (B1) has a linear structure and a structure in which hydrogen is directly bonded to Si (≡Si-H), and is a polymer that undergoes a hydrosilylation reaction with the vinyl groups of the vinyl group-containing organopolysiloxane (A) and with vinyl groups of the components blended into the silicone rubber-based curable composition, thereby crosslinking these components.
[0062] The molecular weight of the linear organohydrogenpolysiloxane (B1) is not particularly limited, but for example, the weight average molecular weight is preferably 20,000 or less, and more preferably 1,000 or more and 10,000 or less.
[0063] The weight average molecular weight of the linear organohydrogenpolysiloxane (B1) can be measured, for example, by gel permeation chromatography (GPC) using chloroform as a developing solvent, in terms of polystyrene.
[0064] Furthermore, it is generally preferred that the linear organohydrogenpolysiloxane (B1) does not contain a vinyl group, which can reliably prevent the crosslinking reaction from proceeding within the molecule of the linear organohydrogenpolysiloxane (B1).
[0065] As the linear organohydrogenpolysiloxane (B1) described above, for example, one having a structure represented by the following formula (2) is preferably used.
[0066] [ka]
[0067] In formula (2), R 4 is a substituted or unsubstituted alkyl group, alkenyl group, aryl group, a hydrocarbon group combining these, or a hydride group having 1 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, and a propyl group, with a methyl group being preferred. Examples of the alkenyl group having 1 to 10 carbon atoms include a vinyl group, an allyl group, and a butenyl group. Examples of the aryl group having 1 to 10 carbon atoms include a phenyl group.
[0068] Also, R 5is a substituted or unsubstituted alkyl group, alkenyl group, aryl group, a hydrocarbon group combining these, or a hydride group having 1 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, and a propyl group, with a methyl group being preferred. Examples of the alkenyl group having 1 to 10 carbon atoms include a vinyl group, an allyl group, and a butenyl group. Examples of the aryl group having 1 to 10 carbon atoms include a phenyl group.
[0069] In addition, in formula (2), multiple R 4 are independent of each other and may be different or the same. 5 The same applies to multiple R 4 and R 5 At least two of these are hydride groups.
[0070] Also, R 6 is a substituted or unsubstituted alkyl group or aryl group having 1 to 8 carbon atoms, or a hydrocarbon group combining these. Examples of alkyl groups having 1 to 8 carbon atoms include methyl groups, ethyl groups, and propyl groups, with methyl groups being preferred. Examples of aryl groups having 1 to 8 carbon atoms include phenyl groups. 6 are independent of each other and may be different from each other or may be the same.
[0071] In addition, R in formula (2) 4 ,R 5 ,R 6 Examples of the substituent include a methyl group and a vinyl group, and a methyl group is preferred from the viewpoint of preventing intramolecular crosslinking reactions.
[0072] Furthermore, m and n are the numbers of repeating units constituting the linear organohydrogenpolysiloxane (B1) represented by formula (2), where m is an integer of 2 to 150 and n is an integer of 2 to 150. Preferably, m is an integer of 2 to 100 and n is an integer of 2 to 100.
[0073] The linear organohydrogenpolysiloxane (B1) may be used alone or in combination of two or more.
[0074] Because the branched organohydrogenpolysiloxane (B2) has a branched structure, it forms regions with high crosslink density, and is a component that significantly contributes to the formation of a sparsely crosslinked structure in the silicone rubber system. Like the linear organohydrogenpolysiloxane (B1), it has a structure in which hydrogen is directly bonded to silicon (≡Si-H), and undergoes a hydrosilylation reaction with the vinyl groups of the vinyl-group-containing organopolysiloxane (A) and with the vinyl groups of other components incorporated into the silicone rubber-based curable composition, forming a polymer that crosslinks these components.
[0075] The specific gravity of the branched organohydrogenpolysiloxane (B2) is in the range of 0.9 to 0.95.
[0076] Furthermore, it is generally preferred that the branched organohydrogenpolysiloxane (B2) does not contain vinyl groups, which can reliably prevent crosslinking reactions from occurring within the molecules of the branched organohydrogenpolysiloxane (B2).
[0077] The branched organohydrogenpolysiloxane (B2) is preferably one represented by the following average composition formula (c).
[0078] Average composition formula (c) (H a (R 7 ) 3-a SiO 1 / 2 ) m (SiO 4 / 2 ) n (In formula (c), R 7 is a monovalent organic group, a is an integer ranging from 1 to 3, and m is H a (R 7 ) 3-a SiO 1 / 2 The number of units, n, is SiO 4 / 2 (the number of units)
[0079] In formula (c), R 7 is a monovalent organic group, preferably a substituted or unsubstituted alkyl group or aryl group having 1 to 10 carbon atoms, or a hydrocarbon group consisting of a combination thereof. Examples of alkyl groups having 1 to 10 carbon atoms include methyl, ethyl, and propyl groups, with methyl being preferred. Examples of aryl groups having 1 to 10 carbon atoms include phenyl groups.
[0080] In formula (c), a is the number of hydride groups (hydrogen atoms directly bonded to Si), and is an integer ranging from 1 to 3, preferably 1.
[0081] In addition, in formula (c), m is H a (R 7 ) 3-a SiO 1 / 2 The number of units, n, is SiO 4 / 2 The number of units.
[0082] The branched organohydrogenpolysiloxane (B2) has a branched structure. The linear organohydrogenpolysiloxane (B1) and the branched organohydrogenpolysiloxane (B2) differ in their structures, that is, whether they are linear or branched. The number of alkyl groups R bonded to Si (R / Si), where the number of Si is 1, is in the range of 1.8 to 2.1 for the linear organohydrogenpolysiloxane (B1) and 0.8 to 1.7 for the branched organohydrogenpolysiloxane (B2).
[0083] Because the branched organohydrogenpolysiloxane (B2) has a branched structure, it leaves a residue amount of 5% or more when heated, for example, in a nitrogen atmosphere to 1000°C at a heating rate of 10°C / min. In contrast, because the linear organohydrogenpolysiloxane (B1) is linear, it leaves almost no residue amount after heating under the above conditions.
[0084] Specific examples of the branched organohydrogenpolysiloxane (B2) include those having a structure represented by the following formula (3).
[0085] [ka]
[0086] In formula (3), R 7 R is a substituted or unsubstituted alkyl group or aryl group having 1 to 8 carbon atoms, or a hydrocarbon group combining these, or a hydrogen atom. Examples of alkyl groups having 1 to 8 carbon atoms include methyl, ethyl, and propyl groups, with methyl being preferred. Examples of aryl groups having 1 to 8 carbon atoms include phenyl groups. 7 Examples of the substituent include a methyl group.
[0087] In addition, in formula (3), multiple R 7 are independent of each other and may be different from each other or may be the same.
[0088] In addition, in formula (3), "-O-Si≡" indicates that Si has a branched structure that spreads three-dimensionally.
[0089] The branched organohydrogenpolysiloxane (B2) may be used alone or in combination of two or more.
[0090] Furthermore, the amount of hydrogen atoms (hydride groups) directly bonded to Si in the linear organohydrogenpolysiloxane (B1) and the branched organohydrogenpolysiloxane (B2) is not particularly limited. However, in the silicone rubber-based curable composition, the total amount of hydride groups in the linear organohydrogenpolysiloxane (B1) and the branched organohydrogenpolysiloxane (B2) is preferably 0.5 to 5 moles, more preferably 1 to 3.5 moles, per mole of vinyl groups in the vinyl group-containing linear organopolysiloxane (A1). This ensures the reliable formation of a crosslinked network between the linear organohydrogenpolysiloxane (B1) and the branched organohydrogenpolysiloxane (B2) and the vinyl group-containing linear organopolysiloxane (A1).
[0091] <<Silica particles (C)>> The silicone rubber-based curable composition of this embodiment may contain silica particles (C).
[0092] The silica particles (C) are not particularly limited, but examples thereof include fumed silica, calcined silica, precipitated silica, etc. These may be used alone or in combination of two or more.
[0093] The silica particles (C) have a specific surface area of, for example, 50 to 400 m2 as measured by the BET method. 2 / g, and 100 to 400m 2 / g. The average primary particle size of the silica particles (C) is, for example, preferably from 1 to 100 nm, and more preferably from about 5 to 20 nm.
[0094] By using silica particles (C) having a specific surface area and average particle size within the above ranges, it is possible to improve the hardness and mechanical strength of the silicone rubber formed, particularly the tensile strength.
[0095] <<Silane coupling agent (D)>> The silicone rubber-based curable composition of this embodiment may contain a silane coupling agent (D). The silane coupling agent (D) may have a hydrolyzable group, which is hydrolyzed by water to form a hydroxyl group, which undergoes a dehydration condensation reaction with the hydroxyl groups on the surface of the silica particles (C), thereby modifying the surface of the silica particles (C).
[0096] The silane coupling agent (D) may also contain a silane coupling agent having a hydrophobic group. This provides the surface of the silica particles (C), thereby reducing the cohesive strength of the silica particles (C) in the silicone rubber-based curable composition and, ultimately, in the silicone rubber (reducing aggregation due to hydrogen bonding via silanol groups). This is thought to result in improved dispersibility of the silica particles in the silicone rubber-based curable composition. This increases the interface between the silica particles and the rubber matrix, enhancing the reinforcing effect of the silica particles. Furthermore, it is thought that the sliding properties of the silica particles within the matrix are improved during deformation of the rubber matrix. The improved dispersibility and sliding properties of the silica particles (C) contribute to improved mechanical strength (e.g., tensile strength, tear strength, etc.) of the silicone rubber.
[0097] Furthermore, the silane coupling agent (D) may contain a silane coupling agent having a vinyl group. This introduces a vinyl group onto the surface of the silica particles (C). Therefore, during curing of the silicone rubber-based curable composition, i.e., when the vinyl groups of the vinyl group-containing organopolysiloxane (A) and the hydride groups of the organohydrogenpolysiloxane (B) undergo a hydrosilylation reaction to form a network (crosslinked structure), the vinyl groups of the silica particles (C) also participate in the hydrosilylation reaction with the hydride groups of the organohydrogenpolysiloxane (B), thereby incorporating the silica particles (C) into the network. This allows for a silicone rubber with a low hardness and a high modulus to be formed.
[0098] As the silane coupling agent (D), a silane coupling agent having a hydrophobic group and a silane coupling agent having a vinyl group can be used in combination.
[0099] Examples of the silane coupling agent (D) include those represented by the following formula (4).
[0100] Y n -Si-(X) 4-n ···(4) In the above formula (4), n represents an integer of 1 to 3. Y represents a functional group having a hydrophobic group, a hydrophilic group, or a vinyl group, and when n is 1, it is a hydrophobic group, and when n is 2 or 3, at least one of the groups is a hydrophobic group. X represents a hydrolyzable group.
[0101] The hydrophobic group is an alkyl group having 1 to 6 carbon atoms, an aryl group, or a hydrocarbon group formed by combining these groups, such as a methyl group, an ethyl group, a propyl group, or a phenyl group, with a methyl group being particularly preferred.
[0102] Examples of the hydrophilic group include a hydroxyl group, a sulfonic acid group, a carboxyl group, and a carbonyl group, and among these, a hydroxyl group is particularly preferred. Although a hydrophilic group may be contained as a functional group, it is preferable that the hydrophilic group is not contained from the viewpoint of imparting hydrophobicity to the silane coupling agent (D).
[0103] Further, examples of the hydrolyzable group include alkoxy groups such as methoxy and ethoxy groups, chloro groups, and silazane groups. Among these, silazane groups are preferred because of their high reactivity with the silica particles (C). Note that, those having a silazane group as the hydrolyzable group have structural characteristics such that (Y n -Si-) structures.
[0104] Specific examples of the silane coupling agent (D) represented by the above formula (4) include those having a hydrophobic group as a functional group, such as alkoxysilanes like methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, and decyltrimethoxysilane; chlorosilanes like methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, and phenyltrichlorosilane; and hexamethyldisilazane. Examples of the vinyl group-containing silane include alkoxysilanes such as methacryloxypropyltriethoxysilane, methacryloxypropyltrimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropylmethyldimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, and vinylmethyldimethoxysilane; chlorosilanes such as vinyltrichlorosilane and vinylmethyldichlorosilane; and divinyltetramethyldisilazane. Among these, taking into consideration the above, hexamethyldisilazane is particularly preferred as the silane having a hydrophobic group, and divinyltetramethyldisilazane is particularly preferred as the silane having a vinyl group.
[0105] <<Platinum or platinum compounds (E)>> The silicone rubber-based hardenable composition of this embodiment may contain platinum or a platinum compound (E). Platinum or platinum compound (E) is a catalytic component that acts as a catalyst during curing. The amount of platinum or platinum compound (E) added is a catalytic amount.
[0106] As the platinum or platinum compound (E), known compounds can be used, such as platinum black, platinum supported on silica or carbon black, chloroplatinic acid or an alcohol solution of chloroplatinic acid, a complex salt of chloroplatinic acid and an olefin, and a complex salt of chloroplatinic acid and a vinylsiloxane.
[0107] The platinum or platinum compound (E) may be used alone or in combination of two or more.
[0108] The silicone rubber-based curable composition of this embodiment may contain an organic peroxide (H). The organic peroxide (H) is a component that acts as a catalyst. The amount of organic peroxide (H) added is a catalytic amount. The organic peroxide (H) can be used in place of the organohydrogenpolysiloxane (B) and platinum or a platinum compound (E), or the organohydrogenpolysiloxane (B) and platinum or a platinum compound (E) can be used in combination with the organic peroxide (H).
[0109] Examples of the organic peroxide (H) include ketone peroxides, diacyl peroxides, hydroperoxides, dialkyl peroxides, peroxyketals, alkyl peresters, peroxyesters, and peroxydicarbonates. Specific examples include benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, p-methylbenzoyl peroxide, o-methylbenzoyl peroxide, dicumyl peroxide, 2,5-dimethyl-bis(2,5-t-butylperoxy)hexane, di-t-butyl peroxide, t-butyl perbenzoate, and 1,6-hexanediol-bis-t-butylperoxycarbonate.
[0110] <<Water(F)>> Furthermore, the silicone rubber-based hardening composition of this embodiment may contain water (F) in addition to the above components (A) to (E).
[0111] Water (F) functions as a dispersion medium to disperse the components contained in the silicone rubber-based curable composition, and also contributes to the reaction between the silica particles (C) and the silane coupling agent (D). This allows the silica particles (C) and the silane coupling agent (D) to be more reliably bonded to each other in the silicone rubber, allowing the composition to exhibit uniform properties overall.
[0112] Furthermore, in addition to the components (A) to (F), the silicone rubber-based curable composition of this embodiment may contain known additive components that are blended into silicone rubber-based curable compositions. Examples include diatomaceous earth, iron oxide, zinc oxide, titanium oxide, barium oxide, magnesium oxide, cerium oxide, calcium carbonate, magnesium carbonate, zinc carbonate, glass wool, and mica. Other additives that may be blended include dispersants, pigments, dyes, antistatic agents, antioxidants, flame retardants, and thermal conductivity improvers.
[0113] The content ratio of each component in the silicone rubber-based hardening composition is not particularly limited, but may be set, for example, as follows:
[0114] In this embodiment, the upper limit of the content of silica particles (C) may be, for example, 60 parts by weight or less, preferably 50 parts by weight or less, and more preferably 35 parts by weight or less, per 100 parts by weight of the total amount of vinyl group-containing organopolysiloxane (A). This allows for a good balance between hardness, tensile strength, and other mechanical strengths. The lower limit of the content of silica particles (C) is not particularly limited, but may be, for example, 20 parts by weight or more, per 100 parts by weight of the total amount of vinyl group-containing organopolysiloxane (A).
[0115] The silane coupling agent (D) is preferably contained in an amount of 5 to 100 parts by weight, more preferably 5 to 40 parts by weight, per 100 parts by weight of the vinyl group-containing organopolysiloxane (A). This ensures that the dispersibility of the silica particles (C) in the silicone rubber-based curable composition is improved.
[0116] The content of organohydrogenpolysiloxane (B) is preferably 0.5 to 20 parts by weight, more preferably 0.8 to 15 parts by weight, per 100 parts by weight of the total of vinyl group-containing organopolysiloxane (A), silica particles (C), and silane coupling agent (D). By keeping the content of (B) within this range, a more effective curing reaction may be achieved.
[0117] The content of platinum or platinum compound (E) refers to the catalytic amount and can be set appropriately. Specifically, it is an amount such that the platinum group metal in this component is 0.01 to 1000 ppm by weight, preferably 0.1 to 500 ppm, per 100 parts by weight of the total amount of the vinyl group-containing organopolysiloxane (A), silica particles (C), and silane coupling agent (D). By ensuring that the content of platinum or platinum compound (E) is at or above the lower limit, the resulting silicone rubber composition can be sufficiently cured. By ensuring that the content of platinum or platinum compound (E) is at or below the upper limit, the curing rate of the resulting silicone rubber composition can be improved.
[0118] The content of the organic peroxide (H) refers to the catalytic amount and can be set appropriately. Specifically, it is, for example, 0.001 parts by weight or more, preferably 0.005 parts by weight or more, and more preferably 0.01 parts by weight or more, per 100 parts by weight of the total amount of the vinyl group-containing organopolysiloxane (A), silica particles (C), and silane coupling agent (D). This ensures a minimum strength as a cured product. The upper limit of the content of the organic peroxide (H) is, for example, 10 parts by weight or less, preferably 5 parts by weight or less, and more preferably 3 parts by weight or less, per 100 parts by weight of the total amount of the vinyl group-containing organopolysiloxane (A), silica particles (C), and silane coupling agent (D). This reduces the effects of by-products.
[0119] Furthermore, when water (F) is contained, its content can be appropriately set, but specifically, for example, it is preferably in the range of 10 to 100 parts by weight, more preferably in the range of 30 to 70 parts by weight, per 100 parts by weight of the silane coupling agent (D), which allows the reaction between the silane coupling agent (D) and the silica particles (C) to proceed more reliably.
[0120] <Silicone rubber manufacturing method> Next, a method for producing the silicone rubber of this embodiment will be described. In the method for producing the silicone rubber of this embodiment, a silicone rubber-based curable composition is prepared, and the silicone rubber can be obtained by curing the silicone rubber-based curable composition. Details are provided below.
[0121] First, the components of the silicone rubber-based hardening composition are mixed uniformly using any kneading device to prepare the silicone rubber-based hardening composition.
[0122] [1] For example, a predetermined amount of vinyl group-containing organopolysiloxane (A), silica particles (C), and silane coupling agent (D) are weighed, and then kneaded using any kneading device to obtain a kneaded product containing these components (A), (C), and (D).
[0123] The kneaded mixture is preferably obtained by first kneading the vinyl group-containing organopolysiloxane (A) with the silane coupling agent (D) and then kneading (mixing) the silica particles (C), which further improves the dispersibility of the silica particles (C) in the vinyl group-containing organopolysiloxane (A).
[0124] Furthermore, when obtaining this kneaded mixture, water (F) may be added to the kneaded mixture of the components (A), (C), and (D) as needed, which allows the reaction between the silane coupling agent (D) and the silica particles (C) to proceed more reliably.
[0125] Furthermore, the kneading of components (A), (C), and (D) is preferably carried out through a first step in which the components are heated at a first temperature and a second step in which the components are heated at a second temperature. This allows the surfaces of the silica particles (C) to be surface-treated with the coupling agent (D) in the first step, and allows by-products formed by the reaction between the silica particles (C) and the coupling agent (D) to be reliably removed from the kneaded mixture in the second step. If necessary, component (A) may then be added to the resulting kneaded mixture, followed by further kneading. This improves the compatibility of the components in the kneaded mixture.
[0126] The first temperature is preferably, for example, about 40 to 120° C., and more preferably, for example, about 60 to 90° C. The second temperature is preferably, for example, about 130 to 210° C., and more preferably, for example, about 160 to 180° C.
[0127] The atmosphere in the first step is preferably an inert atmosphere such as a nitrogen atmosphere, and the atmosphere in the second step is preferably a reduced pressure atmosphere.
[0128] Furthermore, the time for the first step is, for example, preferably about 0.3 to 1.5 hours, more preferably about 0.5 to 1.2 hours, and the time for the second step is, for example, preferably about 0.7 to 3.0 hours, more preferably about 1.0 to 2.0 hours.
[0129] By setting the conditions for the first and second steps as described above, the above-mentioned effects can be more significantly obtained.
[0130] [2] Next, predetermined amounts of organohydrogenpolysiloxane (B) and platinum or a platinum compound (E) are weighed out, and then, using any kneading device, components (B) and (E) are kneaded into the mixture prepared in step [1] above, thereby obtaining a silicone rubber-based curable composition. The obtained silicone rubber-based curable composition may be a paste containing a solvent.
[0131] When kneading components (B) and (E), it is preferable to first knead the mixture prepared in step [1] with the organohydrogenpolysiloxane (B), and then knead the mixture prepared in step [1] with platinum or a platinum compound (E), and then knead the respective mixtures together. This ensures that components (A) to (E) are dispersed in the silicone rubber-based curable composition without promoting the reaction between the vinyl group-containing organopolysiloxane (A) and the organohydrogenpolysiloxane (B).
[0132] The temperature at which the components (B) and (E) are kneaded is, for example, preferably about 10 to 70°C, more preferably about 25 to 30°C, as the roll temperature.
[0133] Furthermore, the kneading time is, for example, preferably about 5 minutes to 1 hour, and more preferably about 10 to 40 minutes.
[0134] In steps [1] and [2], by maintaining the temperature within the above range, it is possible to more effectively prevent or inhibit the progress of the reaction between the vinyl group-containing organopolysiloxane (A) and the organohydrogenpolysiloxane (B). Furthermore, by maintaining the kneading time within the above range in steps [1] and [2], it is possible to more reliably disperse the components (A) to (E) in the silicone rubber-based curable composition.
[0135] The kneading device used in each of steps [1] and [2] is not particularly limited, but for example, a kneader, a two-roll mill, a Banbury mixer (continuous kneader), a pressure kneader, etc. can be used.
[0136] Furthermore, in step [2], a reaction inhibitor such as 1-ethynylcyclohexanol may be added to the kneaded mixture, which makes it possible to more effectively prevent or inhibit the reaction between the vinyl group-containing organopolysiloxane (A) and the organohydrogenpolysiloxane (B) even when the temperature of the kneaded mixture is set at a relatively high temperature.
[0137] In step [2], an organic peroxide (H) may be added in place of the organohydrogenpolysiloxane (B) and platinum or platinum compound (E), or in combination with the organohydrogenpolysiloxane (B) and platinum or platinum compound (E). The preferred conditions, such as temperature and time, and the apparatus used when kneading the organic peroxide (H) are the same as those used when kneading the organohydrogenpolysiloxane (B) and platinum or platinum compound (E).
[0138] [3] Next, the silicone rubber-based hardening composition is hardened to form a silicone rubber.
[0139] In this embodiment, the curing step of the silicone rubber-based curable resin composition is carried out by, for example, heating at 100 to 250°C for 1 to 30 minutes (primary curing), followed by post-baking at 200°C for 1 to 4 hours (secondary curing). The silicone rubber of this embodiment is obtained through the steps described above.
[0140] As a result of investigations, the present inventors have discovered the following: It has been found that reducing the amount of filler in silicone rubber can reduce hardness and tensile stress, but at the same time, it also reduces tear strength and the durability of the silicone rubber.
[0141] After extensive research, we discovered that by appropriately selecting a resin composition, such as the vinyl group-containing organopolysiloxane (A), we can control the crosslink density and uneven distribution of the crosslinked structure, thereby achieving low stress and low hardness across a wide strain range while increasing the tear strength of the silicone rubber. We also found that the tensile strength of the silicone rubber can be increased. While the detailed mechanism is unclear, we believe that the combined use of a high-vinyl group-containing organopolysiloxane and a low-vinyl group-containing organopolysiloxane allows us to control the uneven distribution of the crosslinked structure, thereby increasing the tear strength of the silicone rubber while reducing the hardness. In this way, by increasing the tear strength while maintaining other physical properties, we can increase the breaking energy of the silicone rubber.
[0142] In this embodiment, it is possible to control the tensile stress, breaking elongation, tensile strength, tear strength, and hardness by appropriately selecting, for example, the type and amount of each component contained in the silicone rubber-based curable composition, the method for preparing the silicone rubber-based curable composition, the method for producing the silicone rubber, and the like. Among these, examples of factors that can be used to set the tensile stress, elongation at break, tensile strength, and tear strength within the desired range include the combined use of a low-vinyl-group-containing linear organopolysiloxane (A1-1) and a high-vinyl-group-containing linear organopolysiloxane (A1-2), the use of a vinyl-group-containing organopolysiloxane (A) having terminal vinyl groups to control the crosslink density of the resin and the uneven distribution of the crosslinked structure, and the timing and ratio of addition of the vinyl-group-containing organopolysiloxane (A), the blending ratio of the silica particles (C), surface modification of the silica particles (C) with the silane coupling agent (D), and the addition of water to more reliably promote the reaction between the silane coupling agent (D) and the silica particles (C).
[0143] In this embodiment, when measuring the tensile stress, elongation at break, tensile strength, and tear strength of the silicone rubber-based curable composition, a cured product of the silicone rubber-based curable composition can be used as the heating and measurement object. For example, the cured product may be a sheet-like silicone rubber (cured product of the silicone rubber-based curable composition) obtained by pressing the silicone rubber-based curable composition at 160°C and 10 MPa for 20 minutes to form it into a sheet with a thickness of 1 mm and subjecting it to a primary curing, followed by heating at 200°C for 4 hours to subject it to a secondary curing.
[0144] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various other configurations can also be adopted. [Example]
[0145] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.
[0146] The raw material components used in the examples and comparative examples shown in Table 1 are as follows. (Vinyl group-containing organopolysiloxane (A)) Low vinyl group-containing linear organopolysiloxane (A1-1): A vinyl group-containing dimethylpolysiloxane (structure represented by formula (1-1) and R 1 (Structure in which only the terminal is a vinyl group) High vinyl group-containing linear organopolysiloxane (A1-2): Vinyl group-containing dimethylpolysiloxane (structure represented by formula (1-1) and R 1 and R 2 is a vinyl group)
[0147] (Organohydrogenpolysiloxane (B)) Momentive: "TC-25D"
[0148] (Silica particles (C)) Silica particles (C): Silica particles (particle size 7 nm, specific surface area 300 m 2 / g), Nippon Aerosil Co., Ltd., "AEROSIL300"
[0149] (Silane coupling agent (D)) Silane coupling agent (D-1): Hexamethyldisilazane (HMDZ), manufactured by Gelest, "HEXAMETHYLDISILAZANE (SIH6110.1)" Silane coupling agent (D-2): Divinyltetramethyldisilazane, manufactured by Gelest, "1,3-DIVINYLTETRAMETHYLDISILAZANE (SID4612.0)"
[0150] (Platinum or platinum compounds (E)) Momentive: "TC-25A"
[0151] (Synthesis of vinyl group-containing organopolysiloxane (A)) [Synthesis Scheme 1: Synthesis of Low-Vinyl-Containing Linear Organopolysiloxane (A1-1)] A low-vinyl-group-containing linear organopolysiloxane (A1-1) was synthesized according to the following formula (5). Specifically, 74.7 g (252 mmol) of octamethylcyclotetrasiloxane and 0.1 g of potassium siliconate were placed in a 300 mL separable flask equipped with a condenser and stirring blade and purged with Ar gas, and the mixture was heated to 120° C. and stirred for 30 minutes. An increase in viscosity was confirmed during this time. The temperature was then raised to 155°C and stirring was continued for 3 hours, after which 0.1 g (0.6 mmol) of 1,3-divinyltetramethyldisiloxane was added and the mixture was further stirred at 155°C for 4 hours. After another 4 hours, the mixture was diluted with 250 mL of toluene and washed three times with water. The washed organic layer was reprecipitated and purified by washing several times with 1.5 L of methanol, and the oligomer and polymer were separated. The resulting polymer was dried overnight under reduced pressure at 60°C to obtain a low-vinyl-group-containing linear organopolysiloxane (A1-1) (Mn = 2.2 × 10 5 , Mw=4.8×105 The vinyl group content calculated by H-NMR spectroscopy was 0.04 mol %.
[0152] [ka]
[0153] [Synthesis Scheme 2: Synthesis of High-Vinyl-Group-Containing Linear Organopolysiloxane (A1-2)] A highly vinyl-containing linear organopolysiloxane (A1-2) was synthesized as shown in formula (6) below by the same procedure as in the synthesis of (A1-1) above, except that 0.86 g (2.5 mmol) of 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane was used in addition to 74.7 g (252 mmol) of octamethylcyclotetrasiloxane. (Mn=2.3×10 5 , Mw=5.0×10 5 The vinyl group content calculated by H-NMR spectroscopy was 0.93 mol %. [ka]
[0154] Example 1: Preparation of silicone rubber-based curable composition In Example 1, a silicone rubber-based curable composition was prepared as follows: First, a mixture of vinyl group-containing organopolysiloxane (A), silane coupling agent (D), and water (F) was pre-kneaded in the proportions shown in Table 1 below, and then silica particles (C) were added to the mixture and further kneaded to obtain a kneaded product (silicone rubber compound). Here, the kneading after adding the silica particles (C) was carried out through two steps: a first step of kneading for 1 hour under a nitrogen atmosphere at 60 to 90°C for the coupling reaction, and a second step of kneading for 2 hours under a reduced pressure atmosphere at 160 to 180°C for the removal of the by-product (ammonia).The mixture was then cooled and kneaded for 20 minutes. Next, 1.81 parts by weight of organohydrogenpolysiloxane (TC-25D) and 0.5 parts by weight of platinum or a platinum compound (TC-25A) were added to 100 parts by weight of the resulting kneaded product (silicone rubber compound), and the mixture was kneaded with a roll to obtain the silicone rubber-based curable composition of Example 1.
[0155] Example 2: Preparation of silicone rubber-based curable composition In Example 2, a silicone rubber-based curable composition was prepared in the same manner as in Example 1. First, a mixture of vinyl group-containing organopolysiloxane (A), silane coupling agent (D), and water (F) was pre-kneaded in the proportions shown in Table 1, and then silica particles (C) were added to the mixture and further kneaded to obtain a kneaded product (silicone rubber compound). Here, the kneading after adding the silica particles (C) was carried out in the same manner as in Example 1. Next, 3.77 parts by weight of organohydrogenpolysiloxane (TC-25D) and 0.5 parts by weight of platinum or a platinum compound (TC-25A) were added to 100 parts by weight of the resulting kneaded product (silicone rubber compound), and the mixture was kneaded with a roll to obtain the silicone rubber-based curable composition of Example 2.
[0156] Example 3: Preparation of silicone rubber-based curable composition In Example 3, a silicone rubber-based curable composition was prepared in the same manner as in Example 1. First, a mixture of vinyl group-containing organopolysiloxane (A), silane coupling agent (D), and water (F) was pre-kneaded in the proportions shown in Table 1, and then silica particles (C) were added to the mixture and further kneaded to obtain a kneaded product (silicone rubber compound). Here, the kneading after adding the silica particles (C) was carried out in the same manner as in Example 1. Next, 4.53 parts by weight of organohydrogenpolysiloxane (TC-25D) and 0.5 parts by weight of platinum or a platinum compound (TC-25A) were added to 100 parts by weight of the resulting kneaded product (silicone rubber compound), and the mixture was kneaded with a roll to obtain the silicone rubber-based curable composition of Example 3.
[0157] Example 4: Preparation of silicone rubber-based curable composition In Example 4, a silicone rubber-based curable composition was prepared in the same manner as in Example 1. First, a mixture of vinyl group-containing organopolysiloxane (A), silane coupling agent (D), and water (F) was pre-kneaded in the proportions shown in Table 1, and then silica particles (C) were added to the mixture and further kneaded to obtain a kneaded product (silicone rubber compound). Here, the kneading after adding the silica particles (C) was carried out in the same manner as in Example 1. Next, 2.26 parts by weight of organohydrogenpolysiloxane (TC-25D) and 0.5 parts by weight of platinum or a platinum compound (TC-25A) were added to 100 parts by weight of the resulting kneaded product (silicone rubber compound), and the mixture was kneaded with a roll to obtain the silicone rubber-based curable composition of Example 4.
[0158] Example 5: Preparation of silicone rubber-based curable composition In Example 5, a silicone rubber-based curable composition was prepared in the same manner as in Example 1. First, a mixture of vinyl group-containing organopolysiloxane (A), silane coupling agent (D), and water (F) was pre-kneaded in the proportions shown in Table 1, and then silica particles (C) were added to the mixture and further kneaded to obtain a kneaded product (silicone rubber compound). Here, the kneading after adding the silica particles (C) was carried out in the same manner as in Example 1. Next, 4.53 parts by weight of organohydrogenpolysiloxane (TC-25D) and 0.5 parts by weight of platinum or a platinum compound (TC-25A) were added to 100 parts by weight of the resulting kneaded product (silicone rubber compound), and the mixture was kneaded with a roll to obtain the silicone rubber-based curable composition of Example 5.
[0159] [Table 1]
[0160] (Making silicone rubber) In Examples 1 to 5, the obtained silicone rubber-based curable compositions were pressed at 170°C and 10 MPa for 10 minutes to form into sheets with a thickness of 2 mm, and subjected to primary curing. Subsequently, the sheets were heated at 200°C for 4 hours to undergo secondary curing. As a result, sheet-shaped silicone rubbers (cured products of the silicone rubber-based curable compositions) were obtained as sheet-shaped elastomers.
[0161] [Comparative Example 1] A chloroprene rubber sheet (2 mm thick, 500 mm wide x 500 mm long, Rubber Product Code 10037) purchased from Fuso Rubber Industries Co., Ltd. was used as the sheet elastomer. Comparative Example 2 A fluororubber sheet (2 mm thick, 300 mm wide x 300 mm long, Rubber product code 10001) purchased from Fuso Rubber Industries Co., Ltd. was used as the sheet elastomer.
[0162] The elastomer sheets obtained in the examples and comparative examples were evaluated based on the following evaluation items.
[0163] (hardness) The obtained elastomer sheet having a thickness of 2 mm was processed into a strip test piece 10 (FIG. 1(a)) having a width of 5 mm, a length of 100 mm and a thickness of 2 mm. The obtained strip test piece 10 was placed on a slide glass so that its shape in top view was rectangular. With both ends of the strip test piece 10 relaxed without being pulled, the hardness A0 of the unstretched central portion 30 of the strip test piece 10 in the width direction was measured at 25°C using a hardness tester 20 (manufactured by Teclock Corporation, product name: Automatic Constant Pressure Loader for Durometer GS-610). The hardness was measured with the base of the hardness tester 20 with the indenter attached pressed parallel to the rectangular surface of the strip test piece 10 .
[0164] Next, a manual stretching machine 100 (a uniaxial stretching machine for film) shown in FIG. 2 was prepared. The manual stretching machine 100 includes a chuck 102, which is one fixed end, and a chuck 104 that is movable in the axial direction of a shaft 110. Both ends of a plate-shaped film can be fixed to the chucks 102 and 104. The chuck 104 moves in the axial direction relative to the chuck 102 while holding the film. Between one fixed end (chuck 102) and the other fixed end 112, a shaft 110 fixed to the fixed end 112 is arranged, and guides 106 and 108 are arranged parallel to and on both sides of the shaft 110. Therefore, the chuck 104 moves along the two guides, allowing for more accurate axial movement. After the chuck 104 is moved in the axial direction to a predetermined position and the distance between the chucks is set to a predetermined value, the chuck 104 can be fixed to the guides 106 and 108 by the fixing parts 114 and 116 .
[0165] Next, both ends of the strip test piece 10 were placed in the chucks 102 and 104 of the manual stretching machine 100, respectively, and the strip test piece 10 was stretched. The distance between the chucks when the strip test piece 10 changed from a relaxed state to a taut state was defined as the initial value D0 (40 mm) (FIG. 1(b)).
[0166] Next, the manual stretching machine 100 is used to adjust the chuck distance D x The strip test piece 10 was stretched until the length reached 60 mm, and after holding for 1 minute, the hardness A at the center 30 of the strip test piece 10 at 50% elongation was measured at 25°C in accordance with JIS K6253 (1997). 50 was measured using a hardness tester 20 (Fig. 1(c)). Next, the manual stretching machine 100 is used to adjust the chuck distance D x The strip test piece 10 was stretched until the length reached 80 mm, and after holding for 1 minute, the hardness A at the center 30 of the strip test piece 10 at 100% elongation was measured at 25°C in accordance with JIS K6253 (1997). 100 was measured using a hardness tester 20. Next, the manual stretching machine 100 is used to adjust the chuck distance D xThe strip test piece 10 was stretched until the length reached 120 mm, and after holding for 1 minute, the hardness A at the center 30 of the strip test piece 10 at 200% elongation was measured in accordance with JIS K6253 (1997) at 25°C. 200 was measured using a hardness tester 20.
[0167] Hardness A0, A 50 , A 100 , and A 200 For each test piece, measurements were taken five times using one sample (strip test piece), and the average value of the measurements was used as the measured value. The average values are shown in Table 2.
[0168] [Table 2]
[0169] [Table 3]
[0170] In Table 3, "-" means that measurement was not possible due to breakage.
[0171] Tensile stress and elongation at break were measured on three samples, and the average of the three values was used as the measured value. Tear strength was measured on five samples, and the average of the five values was used as the measured value. The average values for each are shown in Table 3.
[0172] <Tear strength> Using the obtained 2 mm thick sheet-like elastomer, crescent-shaped test pieces were prepared in accordance with JIS K6252 (2001) at 25°C, and the tear strength of the obtained crescent-shaped test pieces was measured (unit: N / mm).
[0173] <Tensile stress> Using the obtained sheet-like elastomer having a thickness of 2 mm, a dumbbell-shaped No. 3 test piece was prepared at 25°C in accordance with JIS K6251 (2004), and the tensile stress M of the obtained dumbbell-shaped No. 3 test piece at 100% elongation was measured at a tensile speed of 500 mm / min. 100 (100% modulus), tensile stress at 200% elongation M 200 The 200% modulus was measured in MPa.
[0174] <Elongation at break> Using the obtained 2 mm thick sheet-like elastomer, dumbbell-shaped No. 3 test pieces were prepared in accordance with JIS K6251 (2004) at 25°C, and the breaking elongation of the obtained dumbbell-shaped No. 3 test pieces was measured. The breaking elongation was calculated by [chuck movement distance (mm)] ÷ [initial chuck distance (60 mm)] × 100. The unit is %.
[0175] <Follow-up ability> First, the following sheet-like test piece 50, concave substrate 60, and Kiriyama funnel 70 were prepared. (50 sheet-shaped test pieces) The sheet-like elastomer of each Example and Comparative Example was used to prepare a sheet-like test piece 50 having a size of 15 cm square and a thickness of 0.5 mm. The shape of the sheet-like test piece 50 in top view was square. (concave substrate 60) A concave substrate 60 was prepared, in which a concave groove 62 was formed in the depth direction from the surface of the substrate. The depth D of the concave groove 62 was 2 mm (FIG. 3(a)), and the diameter (width W) of the concave groove 62 was 20 mm (FIG. 3(b)). As shown in FIG. 3(b), the shape of the concave substrate 60 in a top view is rectangular, and the shape of the concave groove 62 in a top view is circular. FIG. 3(b) is a view taken along the line AA in FIG. 3(a) (a cross-sectional view in a direction perpendicular to the top view). (Kiriyama Rohto 70) The Kiriyama Funnel 70 used was model S-60. The Kiriyama Funnel 70 had an inner width of the mouth end of 85 mm and an inner height H of the mouth of 53 mm.
[0176] Next, the sheet-like test piece 50 was placed on the prepared concave substrate 60 so as to cover the concave groove 62. Next, the opening end of a Kiriyama funnel 70 was pressed against the periphery of the sheet-like test piece 50 (FIG. 3(a)).
[0177] Next, the pressure inside the mouth of the Kiriyama funnel 70 was reduced to 300 mmHg (FIGS. 3(c) to 3(e)). Under such reduced pressure, the conformability of the sheet-like test piece 50 to the inner wall of the mouth of the funnel was evaluated based on the following evaluation criteria. The evaluation results are shown in Table 4.
[0178] (Evaluation criteria) In Figure 3(c), the sheet-like test piece 50 expanded when the pressure was reduced and reached the entire surface of the inner wall of the mouth, and was marked with a ◎; in Figure 3(d), the sheet-like test piece 50 reached part of the upper surface of the inner wall of the mouth but not the entire surface, and in Figure 3(e), the sheet-like test piece 50 did not even reach the upper surface of the inner wall of the mouth, and was marked with an ×.
[0179] [Table 4]
[0180] It was found that the elastomers (silicone rubbers) of Examples 1 to 5 had superior conformability to uneven surfaces compared to Comparative Examples 1 and 2. It is expected that such elastomers of Examples 1 to 5 will be suitable for use in wearable devices that require conformability, particularly in stretchable members of wearable devices. [Explanation of symbols]
[0181] 10 Strip test piece 20 Hardness meter 30 Center 50 sheet test pieces 60 concave board 62 Groove 70 Kiriyama Roth 100 manual stretching machine 102 Zipper 104 Zipper 106 Guide 108 Guide 110 axes 112 Fixed end 114 Fixing part 116 Fixing part
Claims
1. An elastomer for a wearable device, comprising: the tensile stress M 100 of the elastomer at 100% elongation, as measured at 25° C. in accordance with JIS K6251 (2004), is 2.2 MPa or more and 7.0 MPa or less; The elastomer is stretched 50% according to the following stretching procedure, and the durometer hardness A of the elastomer at 50% stretch is measured at 25° C. in accordance with JIS K6253 (1997) using a hardness tester. 50 is 20 or more and 80 or less. (Decompression Operation) (1) A rectangular test piece of a predetermined thickness is prepared from the elastomer. (2) Both ends of the strip test piece are placed between the chucks of a stretching machine. (3) The chuck distance when the strip test piece changes from a loose state to a taut state is the initial value D 0 Let us assume that. (4) Initial value D 0 The chuck distance is increased by a predetermined percentage, and the strip test piece is held in this state for one minute while being elongated by the predetermined percentage.
2. 2. The elastomer of claim 1 , The elastomer is stretched to 100% according to the above-mentioned stretching operation, and the durometer hardness A of the elastomer at 100% stretching is measured at 25°C using a hardness tester in accordance with JIS K6253 (1997). 100 is 25 or more and 85 or less.
3. 3. The elastomer according to claim 1 or 2, The elastomer is stretched to 200% according to the above-mentioned stretching operation, and the durometer hardness A of the elastomer at 200% stretching is measured at 25°C using a hardness tester in accordance with JIS K6253 (1997). 200 is 30 or more and 90 or less.
4. The elastomer according to any one of claims 1 to 3, The tensile stress M of the elastomer at 200% elongation when measured at 25°C in accordance with JIS K6251 (2004) 200 The elastomer has a modulus of elasticity of 0.5 MPa or more and 9.0 MPa or less.
5. The elastomer according to any one of claims 1 to 4, ((M 200 -M 100 ) / M 100 ) × 100 is 10% or more and 110% or less. The above M 100 : The tensile stress M of the elastomer at 100% elongation when measured at 25 ° C. in accordance with JIS K6251 (2004) 100 Shows. The above M 200 : The tensile stress M of the elastomer at 200% elongation when measured at 25 ° C. in accordance with JIS K6251 (2004) 200 Shows.
6. The elastomer according to any one of claims 1 to 5, The elastomer has a tear strength of 25 N / mm or more when unstretched at 25°C, as measured in accordance with JIS K6252 (2001).
7. The elastomer according to any one of claims 1 to 6, An elastomer made of silicone rubber.
8. The elastomer according to any one of claims 1 to 7, An elastomer comprising an inorganic filler.
9. The elastomer according to any one of claims 1 to 8, Elastomers used in elastic components for wearable devices.
10. A wearable device comprising the elastomer according to any one of claims 1 to 9.